The National Emergency gynecoobstetric hospital Edgardo Rebagliati Martins IPSS - Malaverry, Héctor (2015)
Objective: To report the activity of a specialized emergency in Gynecology and Obstetrics. Location: Obstetrical Emergency Service at Edgardo Rebagliati Martins National Hospital (HNERM) of the Peruvian Social Security Institute. Patients and interventions: 19 856 attended and 13 486 hospitalized patients and 4 064 surgical interventions performed during 1994. Results: Average attention was 57 patients per day, 68% requiring hospitalization. Average patient was 31,7 years old with 2,4 pregnancies. The 3 200 cesarean sections represented 8,8 cesarean sections per day and 69,5% of all surgical interventions. Cesarean prevalence at HNERM was 35,45% in 1994, and 9O% of the cases were attended at the Obstetrical emergency. First cause of cesarean section was previous cesarean section (26%). Main cause of the 25 hysterotomies were premature rupture of membranes, fetal demise and abruptio placentae. Main cause of hysterectomy was uterine atony, in 7 of the 17 cases (41%). Conclusions: HNERM’s Obstetrical Emergency's intense activity includes delicate and frequently complex cases and merits recognition to his medical personnel by rendering technological facilities for faster and more precise diagnosis.